SEBUAH KARYA FILM PENDEK “TOPLES KACA” - Arianto Prabowo; Riky Riky; Wahyu Saputra; Arryadianata Arryadianata (Inter Community: Journal of Communication Empowerment, 2019)
The film "Toples Kaca" offers a story about the anxiety of a student who intends to prevent a child from dropping out of school, but a child thinks of quitting school, in the end the student can prevent in his way. The film "Toples Kaca" is in a decision, associated with controlling life as a journey. The content in this film is about the journey of the main character who continues to have strong ambitions and determination towards children. Their aim is to continue to provide encouragement and motivation, even if only by playing and with interactive media a glass jar. Student anxiety from existing patterns, where yes, questioning life, dreams, and future. This pattern is not just an existing system, but more broadly as a whole of economic factors, plus the problem of limitations, lack of encouragement or motivation from parents, children told to work, or the condition of the children themselves who choose to work. Besides "melancholy" in the midst of unrest is the look and mood that we can capture in outline of this film.